1977
DOI: 10.1002/cpt1977213343
|View full text |Cite
|
Sign up to set email alerts
|

Aging and ethanol metabolism

Abstract: The effect of aging on the distribution and elimination of ethanol was studied in a group of 50 healthy subjects ranging in age from 21 to 81 yr (mean, 53.3). Ethanol was administered in a continuous 1-hr infusion at a mean rate of 375 mg/m2 body surface area/min (equivalent to a mean dose of 0.57 gm/kg body weight). Serial blood samples for the determination of ethanol concentration was obtained at 15- to 30-min intervals for up to 4 hr post infusion. Ethanol elimination and distribution were evaluated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
141
1
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 333 publications
(149 citation statements)
references
References 12 publications
3
141
1
1
Order By: Relevance
“…The body's tolerance for alcohol decreases with age and so the equivalent amount of alcohol leads to a higher blood alcohol concentration in older individuals compared to younger (Novier et al, 2015;Vestal et al, 1977). In older adults, alcohol consumption can potentially harm health through increasing the risk of falls and accidents, interactions with medications, and complications related to various diseases (Heuberger, 2009;Immonen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The body's tolerance for alcohol decreases with age and so the equivalent amount of alcohol leads to a higher blood alcohol concentration in older individuals compared to younger (Novier et al, 2015;Vestal et al, 1977). In older adults, alcohol consumption can potentially harm health through increasing the risk of falls and accidents, interactions with medications, and complications related to various diseases (Heuberger, 2009;Immonen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] The elderly are more vulnerable to the effects of alcohol in the organism, in comparison with the younger adults, due to physiological changes associated with aging (decrease of the body's water volume, decrease in the functional capacity of the kidneys and the liver), 6 the increased risk of comorbidity 7,8 and of drug interactions. 7 It is recommended that the consumption of alcohol among older adults does not exceed one drink per day, or, not more than seven drinks a week.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sensitivity of elderly subjects to the toxic effects of EtOH appears to be enhanced compared to younger persons [6][7][8][9]. Laboratory animal studies have also indicated that ethanol metabolism is decreased and toxicity increased with advancing age [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%